(untitled) (Ustozlar uchun, 2026)
Gingivitis and periodontitis, often grouped under the common term periodontal diseases, are persistent infections of the periodontal tissues associated with biofilms (1,3). Between 20 and 50 percent of people worldwide suffer from periodontal diseases, with severe periodontitis being one of the main causes of tooth loss (4). Surgical and conservative approaches are used to treat gingivitis and periodontitis (5,6). A significant number of adjuvant medications have been proposed to improve the clinical course after primary treatment, used in combination with primary therapeutic approaches (7). These adjuvants include various anti-inflammatory, antibacterial, and antiseptic compounds, such as chlorhexidine and essential oils. Other substances that can contribute to tissue regeneration and repair include hyaluronic acid (HA) and enamel matrix proteins.